The Influence of Managerial Ownership, Institutional Ownership, Independent Commissioners and Company Size on Tax Aggressiveness in Food and Beverage Companies on the Indonesia Stock Exchange - Novi Duwi Lestari; Ariyani (Jurnal Ekonomi, 2023)
This study aims to analyze the Effect of Managerial Ownership, Institutional Ownership, Independent Commissioners and Company Size on Tax Aggressiveness in Food and Beverage Sector Companies on the Indonesia Stock Exchange 2017 – 2021. This research uses a quantitative approach. The sampling technique uses purposive sampling which is a technique for determining samples with certain criteria. Source of data used in this research is secondary data. Secondary data, namely data obtained from existing data in the company as an object of research and supported by literature consisting of the internet, articles, and books that are related to research. Secondary data in this study is data on food and beverage companies listed on the IDX for 2017-2021. The results of testing the first hypothesis (H1) show that Managerial Ownership Has an Effect on Tax Aggressiveness. The results of testing the second hypothesis (H2) show that Institutional Ownership Has an Effect on Tax Aggressiveness. The results of testing the third hypothesis (H3) show that Independent Commissioners have an Influence on Tax Aggressiveness, the results of testing the fourth hypothesis (H4) show that company size has an effect on tax aggressiveness. The results of testing the fifth hypothesis (H5) show that managerial ownership, institutional ownership, independent commissioners and company size have a simultaneous effect on tax aggressiveness. This research is still limited to several independent variables, namely managerial ownership, institutional ownership, independent commissioners and company size and this research is still limited in using food and beverage companies on the Indonesia Stock Exchange from 2017 to 2021. This research is expected to provide inputs and contributions of ideas regarding the understanding of taxation related to tax aggressiveness.